Rice Bran Fermented with Kimchi-Derived Lactic Acid Bacteria Prevents Metabolic Complications in Mice on a High-Fat and -Cholesterol Diet - Park, Sihoon (Foods, 2021)
This aim of this study was to investigate the potential beneficial effects of rice bran powder, fermented by Weissella koreensis DB1 isolated from kimchi, to protect against obesity and dyslipidemia induced by a high-fat and high-cholesterol diet, in a mouse model. Male mice were fed a modified AIN-93M diet containing high fat/high-cholesterol (HFCD), or same diet supplemented with non-fermented rice bran powder (HFCD-RB) or fermented rice bran powder (HFCD-FRB) for 10 weeks. In the HFCD-FRB group, body weight, liver and white fat pads weights, triglyceride (TG), total cholesterol (TC), non-high-density lipopreotein cholesterol (non-HDL-C), insulin, glucose and leptine levels in serum, TG levels and the ratio of fat droplets in the liver, TG levels and fat cell size in adipose tissue were decreased, and (high-density lipopreotein cholesterol) HDL-C and adiponectin levels in serum were increased, compared with the HFCD group. The HFCD-FRB group had significantly lower CCAAT-enhancer-binding potein α (C/EBPα), sterol regulatory element-binding transcription protein-1c (SREBP-1c), fatty acid synthase (FAS), and acetyl CoA carboxylase (ACC) gene expression when compared to the HFCD group. The anti-obesity and hypolipidemic effects were marginally greater in the HFCD-FRB group than in the HFCD-RB group. These results suggest that fermented rice bran powder by Weissella koreensis DB1 may have potential beneficial effects on the obesity-related abnormalities and the dysfunction of lipid metabolism.